Urban Development of Rab - a Hypothesis - Budak, Neven (Array, 2006)
The article presents a hypothesis about the urban development of the town of Rab on the island in the Adriatic sea bearing the same name. The main idea is that the Roman nucleus comprized only a smaller part of the later medieval town, opposite to the prevailing opinion that the surface of the Roman town was identical with the medieval one.